Assessing the Vulnerabilities of Mobile Banking Applications and Developing Strategies to Improve Their Security - Hossain, Mohammad Amir; Raza, Md. Adil; Mahjabeen, Farhana; Rahman, Jami Yaseer (PT FORMOSA CENDEKIA GLOBAL, 2025)
Mobile banking apps have changed the way financial services are provided, allowing users to perform banking operations from anywhere. Though this progress has granted consumers unprecedented convenience, it has also opened new doors to vulnerabilities creating an ideal target for hackers on mobile banking applications. It explores the security issues, vulnerable regions of mobile banking applications such as using insecure communication, weak authentication, unprotected storage, and susceptible to malware. Through empiric testing and existing vulnerability assessment frameworks, critical vulnerabilities and their potential consequences on user data and financial systems are identified. It also recommends specific measures to reduce these vulnerabilities, such as upgraded encryption protocols, multifactor authentication (MFA), secure coding strategies and realtime threat monitoring. Through the identification and exploration of these vulnerabilities, the study seeks to contribute to the ongoing efforts of enhancing the security and resilience of mobile banking applications, which ultimately protects user trust and ensures adherence to regulatory standards.